Pediatric patients with COVID-19: A retrospective single-center experience - SANCAR, MESUT (My University, 2022)
Objectives: The pandemic of coronavirus disease 2019 (COVID-19) is still effective all over the world. Compared to adults, data on pediatric patients are limited. In this study, we aimed to retrospectively examine the demographic, clinical, and laboratory characteristics of pediatric patients who were followed up with the diagnosis of COVID-19 in the first 3 months of the pandemic in our hospital. Methods: A total of 190 patients, aged 1 month–18 years, who were followed up with a definite/probable diagnosis of COVID-19, who were treated in the Pediatric Infection Clinic, were included in the study. The demographic features, clinical characteristics, and laboratory findings of the patients were retrospectively analyzed from their electronic medical records. Results: Eighty (42.1%) of the patients were laboratory confirmed (Polymerase chain reaction positive in nasopharyngeal swab). Mean age was 72 (2–216 months) and 102 (53.7%) patients were female. Family contact history was present in 115 (60.5%) patients. The patients were classified as asymptomatic (5.8%), mild (73.2%), moderate (18.4%), and severe/critical (2.6%) according to the severity of the disease. The most common symptoms were cough (71.1%) and fever (51.1%). Hydroxychloroquine alone or in combination was the most commonly used agent. Conclusion: In our study, in which we examined the pediatric COVID-19 patients, most of the patients had a mild clinical course, but there were applications with different clinical pictures such as acute appendicitis. Therefore, COVID-19 infection, which is still very unknown, will continue to surprise us with both changing treatment protocols and clinical presentations such as multisystem inflammatory syndrome in children.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Family Practice; Fundamentals and Skills; General Health Professions; Pathophysiology; Internal Medicine; Assessment and Diagnosis; Medicine (miscellaneous); General Medicine; Children; COVID-19; hydroxychloroquine; multisystem inflammatory syndrome in children; Turkey; Children; COVID-19; hydroxychloroquine; multisystem inflammatory syndrome in children; Turkey